High pressure inactivation of selected avian viral pathogens in chicken meat homogenate. (March 2017) - Buckow, Roman; Bingham, John; Daglas, Susie; Lowther, Sue; Amos-Ritchie, Rachel; Middleton, Deborah
Abstract: High pressure processing was investigated as a means to inactivate avian viral pathogens in chicken meat homogenate. Preliminary studies were conducted on eight viruses: avian influenza virus (AIV), Newcastle disease virus (NDV) and six strains of infectious bursal disease virus (IBDV). Application of 600 MPa at room temperature for up to 2 min resulted in substantial decline of virus infectivity of all strains of IBDV, AIV and NDV in chicken meat homogenate. An inactivation kinetic of IBDV-Tasik94, a very virulent strain of IBDV, showed 5 to 6 log10 reduction of 50% egg infectious doses (EID50 )/0.2 ml in chicken meat homogenate within 10–15 s treatment at 600 MPa and room temperature. However, when measured in eggs, around 0.5 to 2.0 log10 EID50 /0.2 ml of infectious virus remained, even after longer treatment times of up to 2.5 min. The inactivation curve was fitted to different kinetic models and a Log-decay model described best the rapid initial decline of infectivity followed by a persistent "tail" of resistant IBDV-Tasik94. Multiple pressure cycles at 600 MPa were not able to further reduce the titre of IBDV in chicken meat homogenate; however, these resistant IBDV particles were not infectious to chickens when challenged via the mucosal route. This study could inform policy on risk assessment of the importation of chicken meat products. Highlights: Inactivation of pathogenic avian viruses during high pressure processing was investigated. Avian influenza, Newcastle disease and six strains of infectious bursal disease virus were tested. 2 min treatment at 600 MPa resulted in substantial inactivation of viruses in chicken meat homogenate. A very virulent strain of infectious bursal disease virus showed some persistent particles. Resistant IBDV particles were not infectious to chickens when challenged via the mucosal route.